Kompensatorische Kontrolle heimlicher Grundrechtseingriffe Entwicklung einer sicherheitsrechtlichen Kontrolldogmatik unter besonderer Berücksichtigung administrativer Kontrollstrukturen - Alt, Frederike (Mohr Siebeck, 2024)
The secret surveillance by intelligence services conflicts with the constitutional principle of limiting power through control. This raises the question of what requirements the constitution imposes to control the legality of the intelligence services and to prevent the violation of fundamental rights. In this work, the author maps out the basic principles of a security law control dogma based on the latest developments in legislation and jurisprudence.
PublicationDate: 20240403
Keywords: Rechtsstaat -- Effektiver Rechtsschutz -- Kreditgenossenschaften -- Sicherheitsrecht -- Nachrichtendienstrecht -- Schutz der Verfassung -- Rechtskontrolle -- Informationspflicht -- Verfassungsrecht und Staatslehre -- Verwaltungsrecht -- Besonderes Verwaltungsrecht